BIOSYNTHESIZE NANOPARTICLES AS ADVANCED NANOCARRIERS FOR TARGETED THERAPEUTIC INTERVENTIONS IN DISEASE MANAGEMENT - JANNAT , A; BALQEES , K; HASNAIN , M; ASHIQ , M; MUZAMMAL , F; JAVAID , Z; SAEED , Z; BAIG , MH; MUMTAZ , T; RAUF , U (Biological and Clinical Sciences Research Journal, 2024)
Biosynthesized nanoparticles have emerged as cutting-edge nanocarriers for targeted therapeutic interventions in illness management, transforming medication delivery and treatment techniques. These nanoparticles provide a biocompatible and sustainable substitute for conventional synthetic processes since they are made utilizing biological systems including fungi, bacteria, and plants. They are perfect candidates for precision medicine because of their innate capacity to lower toxicity and increase bioavailability. Because of their distinct surface characteristics, biosynthesized nanoparticles are easily functionalized with therapeutic drugs, allowing for targeted distribution to sick cells or certain organs while reducing off-target effects. Additionally, the large surface area-to-volume ratio and nanoscale size promote better cellular absorption and regulated drug release, enhancing therapeutic efficacy. These nanoparticles' natural origin lowers their immunogenicity and adverse response risk, which enhances patient outcomes even more. Biosynthesized nanoparticles have demonstrated great promise in cancer therapy, including the ability to target tumor cells specifically, carry chemotherapy medications, and even combine with imaging agents for theragnostic uses. They also show promise in improving therapy specificity and lowering adverse effects in other diseases like infectious diseases, cardiovascular ailments, and neurological disorders. This study covers the developments in biosynthesized nanoparticles as nanocarriers, highlighting their importance in altering illness management through tailored therapeutics while evaluating the limitations and future prospects for their clinical translation.